Postoperative Catheterization after Total Vaginal Hysterectomy: Six versus Twenty Four Hours. A Randomized Controlled Trial: Kateterisasi Pascaoperasi Total Vaginal Histerektomi: Enam Jam versus Dua Puluh Empat Jam. Sebuah Penelitian Randomisasi Terkontrol - Suskhan Djusad; Abraham A.L. Maukar; Surahman Hakim; Tyas Priyatini; Budi I. Santoso; Leonardo Leonardo (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstracts Objective: To find out whether urinary bladder catheterization after total vaginal hysterectomy is more advantageous.Methods: Forty-six subjects were included. Subjects were divided into two groups. In one group (n = 24), a transurethral catheter was removed after six hours post-surgery. In the other group (n = 24), the catheter was removed after twenty-four hours. A few hours after removal of the catheter, patients were asked to urinate. Then residual volumes were measured by measuring cylinder, using 12F catheter. Pain was measured using visual analogue scale (VAS) score. Patients’ length of stay was also compared. Data were analyzed using Student T-test if distributed normally or Mann-Whitney Rank if data was abnormal.Results: Mean age for each group was 63,21 ± 8,73 and 62,38 ± 7,52 (6 hours, 24 hours respectively). Median score for 6 hours group was 50,00 (range 5 - 80) and for 24 hours was 100 (range 30 - 250) (P = 0,000). Pain perception and hospital stay were not statistically different in both group (P = 0,134 and P = 0,377)Conclusion:In this study, difference in postoperative catheterization time is associated with residual volume. Keywords: bladder catheterization, postoperative catheterization, residual volume, total vaginal hysterectomy. Abstrak Tujuan: Untuk membandingkan lama waktu pemasangan kateter paskaoperasi total vaginal histerektomi yang lebih menguntungkan.Metode: Empat puluh enam pasien ikut serta dalam penelitian. Secara acak dibagi menjadi 2 kelompok. Pada grup I (n = 24), pelepasan kateter dilakukan setelah enam jam pascaoperasi. Pada grup II (n = 24), kateter dilepas setelah dua puluh empat jam. Beberapa jam setelah pelepasan kateter, pasien diminta untuk buang air kecil. Lalu residu urin diukur setelahnya menggunakan gelas ukur, memakai kateter no. 12 F. Skor nyeri menggunakan skor Visual Analogue Scale (VAS). Lama rawat inap juga dibandingkan. Analisis data menggunakan student's T-test. Jika terdistribusi tidak normal, analisis memakai Mann-Whitney Rank.Hasil: Rerata usia untuk tiap grup adalah 63,21 ± 8,73 dan 62,38 ± 7,52 (6 jam, 24 jam, secara berurutan). Skor median untuk grup 6 jam adalah 50,00 (range 5 – 80) dan grup 24 jam adalah 100 (range 30 – 250) (P = 0,000). Tidak ada perbedaan signifikan secara statistic pada rasa skor nyeri dan lama rawat inap (P = 0,134 dan P = 0,377).Kesimpulan: Pada penelitian ini, perbedaan waktu pemasangan kateter pascaoperasi memiliki hubungan dengan volume sisa urine.Kata kunci: kateterisasi urine, kateterisasi pascaoperasi, volume sisa urine, total vaginal histerektomi.